2020
DOI: 10.3390/plants9091180
|View full text |Cite
|
Sign up to set email alerts
|

On the Physicochemical Characteristics and Applications of an “Undesirable” Pyrenean Thorny Cushion Dwarf: Echinospartum horridum (Vahl) Roth

Abstract: Small evergreen shrubs of the family Fabaceae represent a large proportion of current Mediterranean mountain vegetation. Their low pastoral value and tendency for encroachment makes these plants undesirable. In this paper, the thermal and chemical characteristics of Echinospartum horridum, a thorny cushion-shaped dwarf shrub native to the French Central Massif and the Pyrenees (particularly dominant in the shrublands of the Pyrenees), have been analyzed with a view to its valorization. Although the higher and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Methyl β-D-glucopyranoside, also known as β-methyl-D-glucoside (MeG) or methyl hexopyranoside (5.8%, Qual 58), is an O-glycosyl compound that has been found as a major compound in the leaves of the alpine herb Geum montanum L. and other plants of the Rosaceae family [52], as well as in Echinospartum horridum (Vahl) Rothm. [53]. It has been suggested that, like other methylated molecules (i.e., methyl-inositols), it might be involved in tolerance to osmotic stress [52].…”
Section: On the Phytochemical Profile Obtained By Gc-msmentioning
confidence: 99%
“…Methyl β-D-glucopyranoside, also known as β-methyl-D-glucoside (MeG) or methyl hexopyranoside (5.8%, Qual 58), is an O-glycosyl compound that has been found as a major compound in the leaves of the alpine herb Geum montanum L. and other plants of the Rosaceae family [52], as well as in Echinospartum horridum (Vahl) Rothm. [53]. It has been suggested that, like other methylated molecules (i.e., methyl-inositols), it might be involved in tolerance to osmotic stress [52].…”
Section: On the Phytochemical Profile Obtained By Gc-msmentioning
confidence: 99%
“…The progress of the SWE process is highly affected by temperature [ 37 ]. High temperature can quickly destroy the structure of raw materials and extract biological macromolecules by reducing the viscosity of the extraction solvent and improving the fluidity of the solvent [ 38 ]. As can be seen from Figure 2 A, the yield of polysaccharides gradually increased as the extraction temperature increased from 110 °C to 150 °C, while the temperature continued to increase the yield of polysaccharides gradually showed a downward trend.…”
Section: Resultsmentioning
confidence: 99%